Evidence‐practice gaps in lung cancer: A scoping review. (13th October 2016) - Rankin, N.M.; McGregor, D.; Stone, E.; Butow, P.N.; Young, J.M.; White, K.; Shaw, T.
Abstract : Lung cancer is a significant international health problem. Aligning clinical practice with evidence‐based guideline recommendations has the potential to improve patient outcomes. This scoping review describes evidence‐practice gaps across the diagnostic and management care pathway for lung cancer. We conducted searches of online databases Medline, PsychInfo, Cinahl and the Cochrane Library to identify studies published between 2008 and 2012. Of 614 articles screened, 65 met inclusion criteria. We identified seven evidence‐practice gaps: (1) delays in timely diagnosis and referral; (2) curative and (3) palliative treatments are under‐utilised; (4) older age and co‐morbidities influence the use of treatments; (5) the benefits of multidisciplinary team review are not available to all lung cancer patients; (6) psychosocial needs are unmet; and (7) early referral to palliative care services is under‐utilised. The scoping review highlighted three key messages: (1) there are significant challenges in the timely diagnosis and referral of lung cancer; (2) curative and palliative treatments, psychosocial support and palliative care are under‐utilised in lung cancer management; and (3) variations in treatment utilisation appear to be associated with non‐disease factors such as patient characteristics, provider practices and the organisation of health care services. Future research should focus on designing interventions to overcome variations in care.